Near Field Communication in Tourism: A Conceptual Paper (The Gaze: Journal of Tourism and Hospitality, 2013)
Modern society is virtually inconceivable without mobile devices and the consequent use of mobile services. The multitude of technologies incorporated in the tiniest space has turned mobile phones, and smart phones in particular, into the Swiss knives of our times. What is currently perceived to be one of the most promising technologies for the future is Near Field Communication (NFC), which will most likely become the standard in mobile devices in the years to come. Due to the novel nature of this technology, the assessment of its importance for the tourism industry is still relatively unclear. The author is one of the first to focus on NFC in tourism, with the aim of introducing NFC technology and drafting first responses to the following questions: What benefit can NFC technology have for tourism and what functionalities can it trigger? What are the possible future applications in tourism and what challenges will tourism be faced with in this respect?The Gaze: Journal of Tourism and Hospitality Vol.5 2013 pp.1-12